2022
DOI: 10.1001/jamanetworkopen.2022.25735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adjunctive Acupuncture on Pain Relief Among Emergency Department Patients With Acute Renal Colic Due to Urolithiasis

Abstract: IMPORTANCE Renal colic is described as one of the worst types of pain, and effective analgesia in the shortest possible time is of paramount importance.OBJECTIVES To examine whether acupuncture, as an adjunctive therapy to analgesics, could accelerate pain relief in patients with acute renal colic. DESIGN, SETTING, AND PARTICIPANTSThis single-center, sham-controlled, randomized clinical trial was conducted in an emergency department in China between March 2020 and September 2020. Participants with acute renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…This ceiling effect has been described by Paterson, who qualitatively evaluated changes in self-perception among patients treated with acupuncture 27. Tu et al examined the effect of acupuncture on the relief of pain among emergency department patients with acute renal colic, explaining the lack of relief observed a possible ceiling effect related to the robust analgesia administered in this setting 28. In the present study, it is possible that a ceiling effect with acupuncture may have been associated with the significant effects of this modality, which may have prevented further relief with the other touch and mind-body therapies.…”
Section: Discussionmentioning
confidence: 82%
“…This ceiling effect has been described by Paterson, who qualitatively evaluated changes in self-perception among patients treated with acupuncture 27. Tu et al examined the effect of acupuncture on the relief of pain among emergency department patients with acute renal colic, explaining the lack of relief observed a possible ceiling effect related to the robust analgesia administered in this setting 28. In the present study, it is possible that a ceiling effect with acupuncture may have been associated with the significant effects of this modality, which may have prevented further relief with the other touch and mind-body therapies.…”
Section: Discussionmentioning
confidence: 82%
“…If participants report severe pain during treatment and follow-up, and have a VAS score higher than 8, they will be allowed to take painkillers. The type, dosage and duration of painkillers taken will be recorded in CRFs 39…”
Section: Resultsmentioning
confidence: 99%
“…Details of the initial study have been published. 11 , 15 It was a single-center, sham-controlled, randomized controlled trial conducted in Beijing Hospital of Traditional Chinese Medicine Affiliated to Capital Medical University. All patients came from the emergency department.…”
Section: Methodsmentioning
confidence: 99%
“… 9 , 10 Our initial study revealed that in the context of administering diclofenac sodium via intramuscular injection, adjunctive acupuncture can increase the response rate (50 % reduction in baseline pain score) during the early time points (0, 5, 10, 15, 20, and 30 min) but not during the later time points (45 and 60 min) when compared to sham acupuncture. 11 Due to the ceiling effect of response, it remains uncertain whether acupuncture can provide sustained pain relief following the response. In order to provide a comprehensive understanding of acupuncture analgesia, this study supplemented the complete pain relief as an outcome indicator for wide range evaluation.…”
Section: Introductionmentioning
confidence: 99%